New corona virus: is just a tip of iceberg? - Narwat, Arvind; Rani, Seema; Bhutani, Garima; Saini, Rahul; Singh, Kamaldeep (International Journal of Basic & Clinical Pharmacology, 2020)
The world is again experiencing a global viral epidemic of zoonotic origin. As of March 30, 785807 confirmed cases of coronavirus disease 2019 (COVID-19) and 37820 deaths had been reported in more than 120 countries. Strenuous efforts are being made by various countries of the world to halt transmission through shutting down transport, quarantining entire cities and enforcing the use of face masks. International flights have been cancelled and affected cruise ships quarantined. As in all outbreaks, there is an urgent need to develop effective diagnostics, therapeutics and vaccines. Several experimental diagnostic platforms are already in use in China and elsewhere. The whole-genome sequence of SARS-CoV-2 has been obtained and shared widely. Several potential treatments have been proposed, however, no antiviral treatment has been approved for the novel coronavirus, and despite two outbreaks of novel coronaviruses in the past two decades, vaccine development is still in its infancy.